Pengaruh Metode Talaqqi terhadap Motivasi Hafalan Al-Qur’an Hadis di MAN 06 Pasaman Barat - Rona Afrina; Bambang Trisno; Fajriyani Arsya; Puti Andam Dewi (Concept: Journal of Social Humanities and Education, 2024)
Based on the framework behind the problem that the writer put forward, the author focuses on the case of the impact of the talaqqi procedure on the motivation to practice for students in the XI MAN 06 West Pasaman category. The aim of this research is to identify whether or not there are effects of mahfuz using talaqqi procedures to encourage students' practice in learning the Al-Qur'an, the words of the Prophet, category XI at MAN 06 West Pasaman. This research is correlational research with a tendency towards quantitative information. The illustration of this research is students in category XI IPS at MAN 06 West Pasaman, totaling 55 people. There is also a sampling technique used, namely overall sampling considering the number of samples is less than one hundred. Before trying the experiment, it is assumed that the researcher has carried out the required experiments in the form of a normality experiment and a homogeneity experiment. After that, continue with the assumption experiment using a simple linear regression experiment. The research results display analysis and reviews of research information as a result of testing assumptions from the coefficients chart to obtain sig numbers. equal to 0.000 ≤ 0.05, as a result it can be concluded that the elasticity of talaqqi procedures (X) influences students' motivation to practice (Y). it is known that tcount is 3.168 ≥ ttable 2.006, so it can be concluded that the elasticity of talaqqi procedures (X) has a positive and important influence on the elasticity of motivation to practice (Y) Ha is obtained. As a result, it can be concluded that the impact of mahfuz using talaqqi procedures is on encouraging students to practice in learning the Al-Qur'an, the words of the prophet, category XI at MAN 06 West Pasaman.